APPLICATION OF HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) IN BRSUD TABANAN NUTRITION INSTALLATION (CASE STUDY ON RICA-RICA CHICKEN PROCESSING) - Ni Kadek Yuli Yantari; Ni Putu Agustini; I Gusti Putu Sudita Puryana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
The concept of ensuring the safety and quality of food that is considered more effective and "safe" and has been recognized internationally as reliability is the HACCP (Hazard Analysis Critical Control Point) food safety management system. In the implementation of hospital food it is necessary to apply HACCP because the food provided is consumed by high-risk consumers. HACCP is defined as a scientific, rational, and systematic approach to identifying, assessing and controlling hazards. This study aims to determine the flow chart, the application of HACCP systems, and find out the results of microbiological analysis at each stage of the chicken rica process at the BRSUD Tabanan. The sample in this study was taken from the admission process to the distribution to patients, then microbiological testing using the MPN method (Most Probable Number) and TPC (Total Plate Count) examination. TPC in the acceptance sample is 730 cfu/gram, in the preparation process 270 cfu/gram, in the process of presentation 490 cfu/gram, in the distribution process in patients 1920 cfu/gram, and at the consumption deadline is 880 cfu/gram, Coliform and E. coli test results in all samples are zero, and Salmonella sp , Shigella sp, Vib. Cholera, and Vib.parahaemolyticus negative. Based on the results of the test chicken rica was declared good or fulfilled the requirements because the TPC standard based on SNI was 1x104/ gram in processed chicken meat and 1x106 / gram in raw chicken meat.Keywords: HACCP (Hazard Analysis Critical Control Point), TPC (Total Plate Count), MPN (Most Probable Number)